CO2 solubility in aqueous solutions containing Na+, Ca2+, Cl−, SO42− and HCO3-: The effects of electrostricted water and ion hydration thermodynamics. (April 2016) - Gilbert, Kimberly; Bennett, Philip C.; Wolfe, Will; Zhang, Tongwei; Romanak, Katherine D.
Abstract: Dissolution of CO2 into deep subsurface brines for carbon sequestration is regarded as one of the few viable means of reducing the amount of CO2 entering the atmosphere. Ions in solution partially control the amount of CO2 that dissolves, but the mechanisms of the ion's influence are not clearly understood and thus CO2 solubility is difficult to predict. In this study, CO2 solubility was experimentally determined in water, NaCl, CaCl2, Na2 SO4, and NaHCO3 solutions and a mixed brine similar to the Bravo Dome natural CO2 reservoir; ionic strengths ranged up to 3.4 molal, temperatures to 140 °C, and CO2 pressures to 35.5 MPa. Increasing ionic strength decreased CO2 solubility for all solutions when the salt type remained unchanged, but ionic strength was a poor predictor of CO2 solubility in solutions with different salts. A new equation was developed to use ion hydration number to calculate the concentration of electrostricted water molecules in solution. Dissolved CO2 was strongly correlated (R 2 = 0.96) to electrostricted water concentration. Strong correlations were also identified between CO2 solubility and hydration enthalpy and hydration entropy. These linear correlation equations predicted CO2 solubility within 1% of the Bravo Dome brine and within 10% of two mixed brines from literature (a 10 wt % NaCl + KCl + CaCl2 brine and a natural Na +, Ca 2+, Cl − type brine with minor amounts of Mg 2+, K +, Sr 2+ and Br − ). Highlights: Measured CO2 solubility in Na +, Cl −, HCO3 -, Ca 2 + and SO4 2 − solutions at high PCO2 . A new equation calculates electrostricted water (mol/kgw) from hydration number. CO2 solubility strongly correlates (R 2 = 0.96) to electrostricted water. Ion electrostriction of water limits its availability for CO2 caging and solvation. Correlations predict CO2 solubility of several mixed brines to within 1–9%.